Comparison of water consumption of four shelterbelts trees in a typical arid oasis, northwest China - Fu, Shuai; Xu, Bingxian; Leng, Yufang; Peng, Yuxin; Tao, Guogen; Tao, Guogen; Li, Lanhai; Tao, Guogen (International Journal of Agricultural and Biological Engineering, 2024)
The shelterbelt is an indispensable barrier to the ecological and economic development of an oasis. Soil moisture, groundwater and irrigation greatly affect the shelterbelt water consumption and development. In this study, the transpiration rate of shelterbelt trees, soil moisture and meteorological data were collected to determine the effects of soil moisture and meteorological factors on the water consumption of different shelterbelt tree species via multivariate statistical methods. The results showed that the water consumption rate was positively correlated with solar radiation, air temperature and precipitation. Moreover, the leaf transpiration rate exhibited the trend of P. Russkii Jabl.˃P. alba˃P. simonii Carr.>P. nigracv, while the average daily water consumption decreased in the order of P. alba>P. Russkii Jabl.>P. simonii Carr.>P. nigracv. The average daily water consumption levels of P. alba, P. Russkii Jabl., P. simonii Carr. and P. nigracv were (9.15±0.92) kg/(tree∙d), (6.95±1.41) kg/(tree∙d), (4.43±1.32) kg/(tree∙d), and (1.58±0.18) kg/(tree∙d), respectively. Over the growing season, the soil water consumption levels of P. alba, P. Russkii Jabl., P. simonii Carr., and P. nigracv in each shelterbelt tree stand reached 674.8, 336.9, 358.1 and 161.7 kg, respectively. More than 96% of the soil moisture lost was provided by the upper 120-cm soil layer. Understanding the influence and contribution of soil water and meteorological factors to shelterbelt water consumption is beneficial for shelterbelt management and protection. Key words: water consumption, irrigation management, shelterbelts, soil moisture, climatic factorsDOI: 10.25165/j.ijabe.20241702.8264Citation: Fu S, Xu B X, Leng Y F, Peng Y X, Tao G G, Li L H. Comparison of the water consumption levels of four shelterbelt tree species in a typical arid oasis in Northwest China. Int J Agric & Biol Eng, 2024; 17(2): 169–176.